Redox Regulating Enzymes and Connected MicroRNA Regulators Have Prognostic Value in Classical Hodgkin Lymphomas - Karihtala, Peeter (Oxid Med Cell Longev, 2017)
There are no previous studies assessing the microRNAs that regulate antioxidant enzymes in Hodgkin lymphomas (HLs). We determined the mRNA levels of redox regulating enzymes peroxiredoxins (PRDXs) I–III, manganese superoxide dismutase (MnSOD), nuclear factor erythroid-derived 2-like 2 (Nrf2), and Kelch-like ECH-associated protein 1 (Keap1) from a carefully collected set of 41 classical HL patients before receiving any treatments. The levels of redoxmiRs, miRNAs known to regulate the above-mentioned enzymes, were also assessed, along with CD3, CD20, and CD30 protein expression. RNAs were isolated from freshly frozen lymph node samples and the expression levels were analyzed by qPCR. mir23b correlated inversely with CD3 and CD20 expressions (p = 0.00076; r = −0.523 and p = 0.0012; r = −0.507) and miR144 with CD3, CD20, and CD30 (p = 0.030; r = −0.352, p = 0.041; r = −0.333 and p = 0.0032; r = −0.47, resp.). High MnSOD mRNA levels associated with poor HL-specific outcome in the patients with advanced disease (p = 0.045) and high miR-122 levels associated with worse HL-specific survival in the whole patient population (p = 0.015). When standardized according to the CD30 expression, high miR212 and miR510 predicted worse relapse-free survival (p = 0.049 and p = 0.0058, resp.). In conclusion, several redoxmiRs and redox regulating enzyme mRNA levels associate with aggressive disease outcome and may also produce prognostic information in classical HL.